PERLINDUNGAN HUKUM TERHADAP HAK TENAGA KERJA WANITA DI PT. BEKA ENGINEERING PANGKALAN KERINCI - BILL CLINTON; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Women workers are given privilege of rights over men because women are undergoing reproductive functions that are not owned by men. Menstruation, pregnancy, childbirth, abortion and breast-feeding are the nature of women that have been given by God Almighty. Therefore, special protection to women are needed , so that the productivity in the workplace and at home is spirited. But in reality at PT. Beka Engineering Pangkalan Kerinci, the rights of women workers are still being ignored by the company. The objective of this thesis was to find out; First ,The legal protection of the rights of women workers, second, The factors inhibiting the legal protection of the rights of women workers.This research was juridical sociological that used the correlation between law and society. This research was conducted at PT. Beka Engineering Pangkalan Kerinci, the population and sample of this research was whole side regarding to the issues in this study, the data were primary, secondary , and tertiary data. The techniques of collection data were interviews, research library, and questionnaires.There were two main things that can be concluded . First, the legal protection of woman workers at PT Beka engineering pangkalan kerinci is still not running well, such the right of freight shuttle, properly bathroom facilities/ wc, nutritious foods and drinks, maternity leave, menstrual leave, decent wage. It started because of the wowen workers themselves didn’t know their rights. It affected they didn’t get the right they should get because they were ignore by their company. Second, the obstacles to granting the rights of women workers of PT. Beka Engineering Pangkalan Kerinci are the lack of budget funds to fulfill the rights, the company’s lack awareness, company’s habit, the motivation of income, the lack of supervision and socialization of labor offices and transmigration, the lack of sanctions’ enforcement as well as the lack of workers’ knowledge themselves about the rights that should be obtained.Keywords: protection of rights - female worker - PT.Beka Engineering